Endovascular thrombectomy with or without intravenous alteplase for acute ischemic stroke due to large vessel occlusion: a systematic review and meta-analysis of randomized trials. Issue 6 (20th June 2022) - Wang, Xin; Ye, Zhikang; Busse, Jason W; Hill, Michael D; Smith, Eric E; Guyatt, Gordon H; Prasad, Kameshwar; Lindsay, M Patrice; Yang, Hui; Zhang, Yi; Liu, Ying; Tang, Borui; et al.
Abstract : Background: Among patients who had an ischaemic stroke presenting directly to a stroke centre where endovascular thrombectomy (EVT) is immediately available, there is uncertainty regarding the role of intravenous thrombolysis agents before or concurrently with EVT. To support a rapid guideline, we conducted a systematic review and meta-analysis to examine the impact of EVT alone versus EVT with intravenous alteplase in patients who had an acute ischaemic stroke due to large vessel occlusion. Methods: In November 2021, we searched MEDLINE, Embase, PubMed, Cochrane, Web of Science, clincialtrials.gov and the ISRCTN registry for randomised controlled trials (RCTs) comparing EVT alone versus EVT with alteplase for acute ischaemic stroke. We conducted meta-analyses using fixed effects models and assessed the certainty of evidence using the GRADE approach. Results: In total 6 RCTs including 2334 participants were eligible. Low certainty evidence suggests that, compared with EVT and alteplase, there is possibly a small decrease in the proportion of patients independent with EVT alone (risk ratio (RR) 0.97, 95% CI 0.89 to 1.05; risk difference (RD) −1.5%; 95% CI −5.4% to 2.5%), and possibly a small increase in mortality with EVT alone (RR 1.07, 95% CI 0.88 to 1.29; RD 1.2%, 95% CI −2.0% to 4.9%) . Moderate certainty evidence suggests that there is probably a small decrease in symptomatic intracranial haemorrhage (sICH) with EVT alone (RR 0.75, 95% CI 0.52 to 1.07; RD −1.0%; 95%CI −1.8% to 0.27%). Conclusions: Low certainty evidence suggests that there is possibly a small decrease in the proportion of patients that achieve functional independence and a small increase in mortality with EVT alone. Moderate certainty evidence suggests that there is probably a small decrease in sICH with EVT alone. The accompanying guideline provides contextualised guidance based on this body of evidence. PROSPERO registration number: CRD42021249873.